Analisis Metode Weighted Aggregated Sum Product Assesment pada Pemilihan Merek Produk Air Mineral - Bei, Fathurachman; Saepudin, Sudin (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Water is one of the sources of life in this world. The benefits of water are of course incalculable, if we relate it to the consumption of water, especially mineral water. Many companies see the business potential of mineral water as a very profitable potential for businessmen. But with the emergence of many brands of drinking water in containers creating very strong competition between companies, this makes it difficult for mineral water consumers to choose which brand to buy, it is necessary to review the mineral water brand that is sold and consumed the most. From these problems, it shows that the importance of a Decision Support System to help buyers of mineral water brand products in determining the choice of brand of goods that is in line with the criteria. The method used in this decision support system research is the WASPAS method. The ranking results of each alternative using the WASPAS method with the final result of the Aqua brand product occupying the first position with a value of 2,441 as a recommendation for the selection of bottled mineral water product brands, and the Club product brand having a value of 2,219 by placing the last of 7 alternative brands of bottled mineral water products. . From these results, it can be concluded that the mineral water brand AQUA is the best choice to increase its stock because it has the highest value of 2,441.